Performance analysis on percentage of wheel slip for a passenger car using GPS and wheel speed sensor - Lawrence, Blasius (2010)
This thesis deals with the analysis on percentage of wheel slip for a passenger car using GPS and wheel speed sensor. The objective of this thesis is to analyze the percentage of wheel slip for a passenger car in a various velocity, road condition and driving mode. The thesis describes the post-processing method to analyze the percentage of wheel slip and identify the effective rolling radius and the longitudinal tire stiffness for maximum tire life and performance. Driving and braking behaviour of vehicle were both studied in this thesis for paved and unpaved sandy road condition which commonly the contributing factors to the wheel slip to occur. The data used for the analysis is obtained through experimental test using UMP Test Car which has been installed with Wheel Pulse Transducer, Global Positioning System and DEWESOFT software for data acquisition purpose. The post-processing method was performed using Flexpro and Microsoft Office Excel. The post-processing method to analyze the percentage of wheel slip was performed using the SAE definition of wheel slip and the percent error in the distance travel by the car between free rolling and actual condition. Finally, the longitudinal force, the effective rolling radius and the longitudinal tire stiffness was determined for both driving and braking maneuver of vehicle on paved and unpaved sandy road condition. From the results, it is observed that the percentage of wheel slip during driving maneuver is higher for unpaved sandy road condition compares to that the paved road. It is also observed that the longitudinal force of the tire is lower for unpaved sandy road compare to the paved road condition. The effective rolling radius of the tire during driving maneuver was determined to be lower compare to the free rolling radius of the tire. During braking manuever, the results show that the percentage of wheel slip is higher for unpaved sandy road compare to that for paved road condition. The longitudinal force and tire stiffness also observed lower for unpaved sandy road condition. The effective rolling radius of the tire during braking determined higher compared to that in the free rolling radius. The results concluded that the percentage of wheel slip is strongly dependent to the longitudinal force and the tire road friction. Therefore, effective rolling radius and longitudinal tire stiffness obtained can significantly use to improve tire design and construction. The results also can be use to improve the energy usage efficiency and fuel consumption of vehicle.